Describing prospective teacher’s promote action In online mathematics learning - Iffah, Jauhara Dian Nurul; Tristanti, Lia Budi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
Promoted action is an activity offered by the teacher to students so that they can develop new knowledge or experience. The promoted action chosen by the teacher will depend on the knowledge possessed by the teacher. It is commonly referred to as pedagogical content knowledge (PCK). In addition, to become a professional teacher with a well-measured PCK, the prospective teacher has been trained since the lecturing process. This study aims to describe promoting the actions of prospective teacher students in learning mathematics online. It is descriptive qualitative research on the subject of four students who take the peer teaching program. Subject selection was based on the PCK criteria of subjects with categories 0-0, 0-1, 1-0, and 1-1, which indicated the order of levels of pedagogical knowledge- content knowledge. Data collection methods are tests to determine the PCK of prospective subjects, observation of the learning process, and documentation of learning records. The triangulation used to see the credibility of the data is time triangulation. The results showed that all subjects elicited promoted actions in motivation, concentration, processing, and exploration phases. The four students have different ways of bringing up encouraging action based on their ability criteria.